Property Rights Transfer of Land Under Government Regulation Number 24 of 1997 on Land Registration in The Semarang City - Ida Fitriany; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
The problem in this research is how the implementation of the transition land ownership through of buying and selling in Semarang?, and What are the barriers and solutions to transition ownership of the land by way of sale and purchase in Semarang? Sociological juridical approach, specification of descriptive analytical research. Source of Data are Primary and Secondary Data. Research technique purposive sampling non-random sampling. Data collection techniques by observation and interviews and conducted through the study of literature. Data Analysis Techniques with qualitative analysis methods.The results of the study in this paper the problem is still a delay in registration of transfer of property rights on land that is done by selling under the counter. Pleased with the legal cover for land buyers when buying and selling is done under the hand and is not registered with the Land Office, it is for the buyer of land is not legally strong / weak and limited. It is the duty of the buyer to complete the land to make a statement of deeds delays, physical mastery statement and the statement is not in dispute. The land buyers are often disadvantaged by the implementation of the sale and purchase under the hand, because when to create a deed, the seller had died or had not known where he lived.Keywords: Sale and Purchase of Land, Transfer of Rights, and Government Regulation No. 24 of 1997 on Land Registration.